Trade Credit Policy and Agency Theory (Global Journal of Management and Business Research, 2014)
The study here provides an agency model to explain the offer of trade credit in an asymmetric environment between the suppliers and the customers. Many theories inform traditional arguments focusing on the existence of the trade credit (e.g. tax theory, transaction cost theory, liquidity theory and product quality theory). One theory studies the adverse selection phenomenon but the moral hazard problem needs exploration. The findings indicate that day of sales outstanding of Tunisian export SMEs relates directly to adverse selection and inversely link to moral hazard measured by provision on bad debts and cost ratio. By testing the traditional models, the study does not confirm tax theory, liquidity theory or transaction cost theory. However, the findings support the product quality theory which is based on ex-ante asymmetric information.
Keywords: trade credit; agency theory; adverse selection; moral hazard; tunisian export smes